2019
DOI: 10.3390/su11195157
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of University Restaurant Menus: A Case Study in Brazil

Abstract: The production of collective meals in institutional restaurants demands a great use of natural resources. The search for strategies to reduce negative environmental impacts in this sector is essential to offer meals that are not only healthy but also sustainable. In this study the evaluation of water footprint (WF) of menus offered in a public university restaurant located in the northeast of Brazil and the verification of the origin of foodstuff purchased to compose the menus in 2 months were carried out. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
1
21
0
9
Order By: Relevance
“…In another study, the same authors found an average WF per capita of 2099.1 liters per meal per day, result close to the average per capita value found in this study [9]. Hatjiathanassiadou et al [34] found WF values per capita of 2752.4 L for traditional lunch menus and 1113.9 L for vegetarian menus. The difference in these values was due to the use of foods of animal origin, mainly beef [34].…”
Section: Menu Water Footprintsupporting
confidence: 88%
See 3 more Smart Citations
“…In another study, the same authors found an average WF per capita of 2099.1 liters per meal per day, result close to the average per capita value found in this study [9]. Hatjiathanassiadou et al [34] found WF values per capita of 2752.4 L for traditional lunch menus and 1113.9 L for vegetarian menus. The difference in these values was due to the use of foods of animal origin, mainly beef [34].…”
Section: Menu Water Footprintsupporting
confidence: 88%
“…Similar to the aforementioned work, a case study conducted in a university restaurant, evaluating the origin of the purchased foodstuffs, showed a notable participation of foods/ingredients from state (49.47%) and regional (15.79%) origin, which were distributed in the categories of vegetables and fruits, milk and dairy products [34]. This finding is in agreement with those found in this research, in which food of local, state and regional origin add up to more than 50.00% of the foodstuffs purchased in all six PEIR evaluated.…”
Section: Foodstuffs Acquisition From the Perspective Of Their Originmentioning
confidence: 59%
See 2 more Smart Citations
“…In Brazil, low-cost food services more frequently hire untrained and low-educational-level food handlers [21,22]. All of these factors can impact the social and economic aspects of sustainability [5,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%